Stress Levels, Emotional Eating, Snacking Habits, and Nutrient Intake among College Students during the COVID-19 Pandemic - Afia, Difa; Dwiriani, Cesilia Meti; Dina, Resa Ana (Jurnal Gizi dan Pangan, 2023)
This study analyzed the correlation between stress levels and emotional eating, snacking habits, and nutrient intake among college students. This cross-sectional study involved 98 students as subjects who were selected by convenience sampling through an online questionnaire. The result showed 70.4% of the subjects experienced moderate stress, 52% were emotional eaters, 64.3% consumed snacks more than 3 times a day, 39.7% had a protein deficit, 36.7% had an excessive fat intake, and 49% had an energy and carbohydrate intake classified as severely deficit. This study found a positive correlation (p=0.04; r=0.21) between stress levels and emotional eating. Among college students, a high prevalence of moderate stress level was associated with emotional eating.